SOCIAL AND SPIRITUAL REFORMS IMPLEMENTED IN NEW UZBEKISTAN - Tursunmurad D. Mamatqabilov (Web of Journals Publishing, 2024)
The article focuses on the issues of building a new Uzbekistan in line with world standards, implementing fundamental reforms in the political, economic, social and spiritual spheres, creating a legal system that will strengthen them with the law.
Keywords: New Uzbekistan, political, economic, social and spiritual life, reform strategy.